Perbedaan Penyesuaian Diri Anak dalam Belajar di Rumah Saat Pandemi COVID-19 Ditinjau dari Dukungan Sosial Orang Tua dan Self Regulation Anak di Kota Gorontalo - Nunung Suryana Jamin; Icam Sutisna; Fitriah Gia; Mutiara Abdullah (LP. Ma'arif Janggan Magetan, 2023)
In this study, the goal to be achieved was to determine differences in children's adjustment to learning at home during the Covid 19 pandemic in terms of parents' social encouragement and children's self-regulation in the city of Gorontalo. The approach used in this research is quantitative. The method used in this study is a survey method using data collection techniques through questionnaires. There are three questionnaires used, namely the child's self-adjustment questionnaire, the parent's social encouragement questionnaire, and the self-regulation questionnaire. The research subjects were 120 parents who had children aged 5-7 years who attended state kindergartens in the city of Gorontalo. The sampling technique uses proportional random sampling, which means that the sampling takes into account the representation of all state kindergarten schools evenly in every sub-district throughout Gorontalo City. The data analysis technique used is a two-way ANOVA hypothesis test. Previously, the data had been tested for validity and reliability as well as assumption tests so that the data produced was completely unbiased and consistent. Hypothesis test results F = 0.683 with p = 0.508 (p <0.05) so there is no interaction between children's self-adjustment and learning at home during the Covid-19 pandemic in terms of parental social support and children's self-regulation. In addition, the results of hypothesis testing between children's adjustment to parental social support obtained F=0.095 with p=0.910 (p<0.05) meaning that there was no difference in child adjustment in terms of parental social support. Likewise, if the hypothesis test between the child's self-adjustment and the child's self-regulation yields F = 0.064 with p = 0.614 (p <0.05) it means that there is no difference in the child's adjustment in terms of the child's self-regulation. So it can be concluded that there is no difference in children's adjustment to learning at home during the Covid 19 pandemic in terms of social support and parental self-regulation both collectively and individually.